Delivering sport science and sport medicine services to regional, rural and remote athletes - Annis-Brown, P.; Ansell, W.; Christensen, S. A.; Woodward, G. (36th Annual State Conference of Sports Medicine Australia (Qld Branch), 24-25 Mar 2007, Caloundra, Australia., 2007)
How do you provide sport science and sport medicine services to young athletes living in the large and sparsely populated New England and North West Region of New South Wales? In the most economical and cost effective manner as possible. However this response typically means minimizing the program costs while tacitly lowering the expectations of what rural, regional, and remote athletes might gain from such a program. In other words, short-changing country athletes compared to what sport science and sport medicine offers their city-cousins living in Brisbane, Sydney, and Melbourne. Putting aside any moral objections to this, country athletes have made a significant contribution to Australia`s sporting heritage and as such we can not afford to under service this talent pool. This paper presents a case study that describes how the Northern Inland Academy of Sport (NIAS) has provided sport physiotherapy, psychology, and nutrition to young athletes living through the north-west region of New South Wales (NSW) via the Regional Athlete Coach Education (RACE) program. The case study displays how the NIAS sport science and sport medicine program has evolved over the past seven years. That is, from being delivered on a sport-by-sport basis following the New South Wales Institute of Sport (NSWIS) model for Tier-3 sports, to employing a town-by-town service delivery system. Part of the innovation of the NIAS RACE program is providing sport physiotherapy, psychology, and nutrition education in local towns throughout north-west NSW. However another part involves inviting NIAS athletes and their families, coaches and friends to be part of this training. This is the service delivery component. But RACE also involves conceptual and technical innovations that present sport science and sport medicine as local, relevant and as accessible to young athletes in Tenterfield, Moree, and Gunnedah as their counterparts in Brisbane, Sydney, and Melbourne. The practical implication of this paper is to display that delivering sport science and sport medicine services to regional, rural and remote athletes needn`t be expensive but it does need to be innovative.